Recombinant expression and purification of coiled-coil bioelastomeric proteins from marine snail egg capsules - Tan, Raymond Yong Tai (2012)
The egg capsules of Busycotypus canaliculatus, that protect the developing embryos from adverse environment conditions and predators, have very unique material properties. From previous studies, it was shown that these egg capsules possess high reversible extensibility and stiffness which has rapid recovery upon extension due to reversible phase transition between α-helix to β-sheets. The egg capsule precursors actually undergo self-assembly and crosslinking prior to their achieving mature form, thus, it is important to study these processes that result in possessing these mechanical properties. The egg capsule is assembled from four main Capsule Proteins (CP1a, CP1b, CP2 & CP3) and their amino acid sequences have been deduced by previous researchers. However, the characterizations were incomplete due to inadequate protein yields after extractions and purifications. To tackle this problem, a microbial system using E. Coli (Escherichia Coli) was successfully established to produce these proteins in high yields, eliminating the need for their direct extraction from B. canaliculatus. For the next step of purification, cation exchange, reverse phase and size exclusion chromatographic techniques were used, starting with CP1a. However, many problems surfaced during the purifications and only some were resolved. CP1a was not sufficiently pure to proceed to the next stage, characterization. Nevertheless, the experimental protocols were sufficiently optimized, approaching >90% purity for CP1a. This work paves the way in the future for the rapid purifications of the remaining egg capsule protein, and offers the potential for the creation of robust biomimetic elastomeric materials.